2019
DOI: 10.1177/1526602819844995
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Syringe Plunger Device Significantly Reduces Guidewire Threading Time Regardless of Experience Level or the Presence of Presbyopia

Abstract: Purpose: To evaluate the efficacy of a new guidewire threading instrument (GTI) in reducing guidewire threading times compared with the traditional freehand method. Materials and Methods: This prospective, controlled, single-center study recruited 100 subjects (mean age 45.2±11.3 years; 43 men) and divided them into 2 groups depending on their professional background: 50 experienced medical personnel (performed or assisted in >50 catheter-based procedures) and 50 medical personnel with no experience in endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The authors utilized the plunger from a conventional 20-mL syringe and modified it by removing both ends of the plunger with a scalpel or scissors. 1 We feel that the additional step of removing both ends of the plunger is not required and may expose the patient to additional risks. The World Health Organization (WHO) published the WHO Guidelines for Safe Surgery in 2009, with an emphasis on preventing inadvertent retention of surgical instruments and sponges in surgical wounds.…”
Section: Letter To the Editorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors utilized the plunger from a conventional 20-mL syringe and modified it by removing both ends of the plunger with a scalpel or scissors. 1 We feel that the additional step of removing both ends of the plunger is not required and may expose the patient to additional risks. The World Health Organization (WHO) published the WHO Guidelines for Safe Surgery in 2009, with an emphasis on preventing inadvertent retention of surgical instruments and sponges in surgical wounds.…”
Section: Letter To the Editorsmentioning
confidence: 99%
“…We read with interest the article by Ysa et al 1 on the use of a modified syringe plunger to reduce guidewire threading times compared with the traditional freehand method. In the article, the authors reported significantly faster guidewire insertion times in both 0.035- and 0.014-inch platforms, regardless of the operator’s prior experience in endovascular techniques.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Removal of both ends exposes the furrows of the plunger and reduces the likelihood of the device rolling across the table, especially when cannulating on a nonflat surface (eg, on the patient), significantly improving stability of the whole system. Finally, the “modified syringe plunger” 3 compared with the former version described by our group 4 results in a less bulky device that facilitates guidewire/catheter manipulation since both hands are comfortably positioned on the table.…”
mentioning
confidence: 99%